The Cauchy Problem for Parabolic Equations with Degeneration - Ivan Pukal’skii; Bohdan Yashan (Advances in Mathematical Physics)
Annotation. For a second-order parabolic equation, the multipoint in time Cauchy problem is considered. The coefficients of the equation and the boundary condition have power singularities of arbitrary order in time and space variables on a certain set of points. Conditions for the existence and uniqueness of the solution of the problem in Hölder spaces with power weight are found.